PENGARUH MODEL PEMBELAJARANPROBINGPROMTING TERHADAP HASIL BELAJAR KEWIRAUSAHAAN YAYASAN PERGURUAN SMKS HARAPAN STABAT T.A 2018/201 - Asih Devi Andriyani (Jurnal Administrasi dan Perkantoran Modern, 2020)
The purposeof this study to know influence of Probing Promting Model on Student’s Learning Output on subjects Entrepreneurship Yayasan Perguran SMKS Harapan Stabat Academic Year 2018/2019.This study is using experimental method. The population in this study is all students of class XI AP which amounted to 140 people. The sample of thisstudy is class XI AP 4 (Experiment) which amount 35 people and XI AP 2 (control) which amount 35 people. The research instrument used to collect data is a test of learning outcomes. Data analysis technique used for normality test is Kolmogorov Smirnov with criterion tcount> ttable at level α = 0,05, whereas hypothesis test using the partial test (t) with the test criterion is tcount> ttable at the level of α = 0.05. The study of data analysis showed that the value of t test of experiment I is 0,996 with a research sig of 0.309> 0.05. This shows that significant 0.309> 0.05, then α 0.000 <0.05. From these results it can be concluded that is a positive and significant influence of learning Probing Promting Model on Students' Learning Outcomes on subjects Entrepreneurship Yayasan Perguran SMKS Harapan Stabat Academic Year 2018/2019.